SOME BIOCHEMICAL ATTRIBUTES IN SEMINAL PLASMA OF IRAQI BUFFALO BULLS AND THEIR RELATION TO THE SEMEN QUALITY - K. S. Musa; T. A. Abdulkareem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was undertaken to figure out the relationship between some biochemical characteristics in seminal plasma with the semen quality of Iraqi buffalo bulls (Bubalus bubalis). Semen was diluted with the Tris extender and divided based on the sperm cell’s individual motility into two groups. The first group included good-semen quality (GS; n=3), whereas, the second group included poor-semen quality (PS; n=5). The differences between GS and BS groups in all seminal biochemical attributes lacked significance. A negative and significant (P≤0.05) correlation coefficient was noticed between cholesterol concentration and both principal and terminal sperms abnormality (r= -0.52), and total abnormalities (r= -0.53). A positive and significant (P≤0.05) correlation coefficient was shown between cholesterol concentration and normal sperm percentage (r= 0.53). Moreover, there was a negative and significant correlation (P≤0.05) between the triglyceride concentration and each of the percentages of individual sperm motility (r = -0.50) and of live sperm (r = -0.51). It can be concluded that some biochemical characteristics of seminal plasma can be used to predict the semen quality and fertility of Iraqi buffalo bulls.